Digital Gathering Spaces: An Exploration of A Facebook Community For TKI/TKW Riyadh dan Jeddah Saudi Arabia And Stories It Reveals - Niyu; Anthony, Marcelyn (Institut Komunikasi dan Bisnis LSPR, 2023)
Communities on social media have become a platform to connect and interact with individuals with the same interests among a variety of groups as well as a forum for interaction to discuss topics aligned with the interests of diverse parties. For Indonesian migrant workers (TKI) in Saudi Arabia, the Facebook community serves as a social media outlet to present and address the issues they encounter. This study aims to investigate the interactions between TKI/TKW and the issues addressed within the Facebook community and examine their stories in digital space. This research employs a qualitative approach with netnography methods. The primary source is the Facebook community of TKI/TKW in Riyadh and Jeddah, Saudi Arabia, and supporting sources are derived from literature studies. The findings revealed that the Facebook community for TKI/TKW in Saudi Arabia is a mechanism for these individuals to share information, obtain emotional support, and provide solutions for TKI/TKW who encounter problems in a way that is understandable to them. As observed where numerous cases of TKI/TKW depict the mistreatment of these domestic workers or stories of troubled migrant workers, the findings reveal that the stories about the obstacles and problems that arise are largely caused by illegal migrant worker. Other findings reflect a single-story narrative does not represent the actual condition of TKI/TKW in Saudi Arabia, more stories are to be revealed. The existence of a Facebook community for TKI/TKW in Saudi Arabia can be a highly advantageous community for its member.